Characterization of the biochemical response of Coffea canephora accessions regarding resistance to orange rust (Research, Society and Development, 2022)
In situations of abiotic or biotic stress, plants tend to activate defense responses, whether structural or biochemical. The objective of this work was to study the interaction of clones of Coffea canephora x Hemileia vastatrix, to identify the host responses in the interaction of incompatibility and compatibility with the pathogen. For that, seedlings with 120 days of age of the clones of the variety BRS 'Ouro Preto' C199, C160 and C125, were inoculated with the pathogen (1.5 x 104 urediniospores/mL) and the plants were taken to the inoculation chamber at 25 °C and 90% relative humidity for up to 168 hours. The data were submitted to analysis of variance and the means were compared by Tukey test at 1% of significance. After the quantification of total proteins, it is possible to observe that in Clones C199 and C160 the first increase in protein content occurred after six hours, with the maximum production peak occurring after 72 hours. And this dispersing slightly only after 120 hours. In the susceptible clone, the response only occurred after 48 hours, which was 20% lower than the resistant variety and there was no second peak of response, of production. For the activities of peroxidase and phenylalanine-ammonia-lyase, a similar response pattern was observed for the clones under study, where an induction of activity and its intensity were higher in these resistant clones. This result suggests that there is a biochemical response involved in rust resistance and this should be especially investigated at 72 hours after inoculation.